SOPAN SANTUN BAHASA SEBAGAI DASAR PENGEMBANG KEPRIBADIAN TUNAS BANGSA - SA, Rini . (Majalah Transformatika, 2009)
Indonesia student represent the new generation of the nation and also owner walk stick the estafette of nation and state responsibility.indonesia student which have personality to have the decent characteristic have language, responsibility, never give up, high minded, discipline. can translate the natural phenomenon and also science, can create the interaction vertically and also horizontal.Â keyword : personality, ability have language, new generation of the nation.